2022
DOI: 10.1098/rsob.210310
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced oxidative stress activates NRF2 to mediate fibronectin disorganization in vascular formation

Abstract: Cigarette smoke significantly induces oxidative stress, resulting in cardiovascular disease. NRF2, a well-known antioxidative stress response factor, is generally considered to play protective roles in cardiovascular dysfunction triggered by oxidative stress. Interestingly, recent studies reported adverse effects of NRF2 on the cardiovascular system. These unfavourable pathogenic effects of NRF2 need to be further investigated. Our work shows that cigarette smoke extract (CSE)-induced oxidative stress disturbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…How Lp(a) can support the development and progression of PAD through intraplaque hemorrhage can only be conjectured. Ex vivo studies show that Lp(a) enhances angiogenesis in the chorioallantoic membrane ( 43 ) and this could synergize with the development of an abnormal angiogenesis observed in smoking ( 44 ) leading to an enhanced plaque development. This pathophysiology might lead to increased bleeding into plaques and contribute to the progress of atherosclerosis in large arteries such as those supplying the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…How Lp(a) can support the development and progression of PAD through intraplaque hemorrhage can only be conjectured. Ex vivo studies show that Lp(a) enhances angiogenesis in the chorioallantoic membrane ( 43 ) and this could synergize with the development of an abnormal angiogenesis observed in smoking ( 44 ) leading to an enhanced plaque development. This pathophysiology might lead to increased bleeding into plaques and contribute to the progress of atherosclerosis in large arteries such as those supplying the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Xue et al (29) shows that exposure of human umbilical vein endothelial cells (HUVECs) to cigarette extract activates Nrf2 expression. In periodontal disease, increased expression of Nrf2 can prevent periodontal tissue from developing periodontitis and alveolar bone damage, (19) and Li et al (30) showed a decrease in Nrf2 expression in the nucleus and cytoplasm of the diabetic periodontitis group compared with the periodontal tissue control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing adhesive structural support, which many cell surface receptors recognize, fibronectin also forms a template to which other ECM proteins and soluble growth factors can bind and assemble. (40) Xue et al (29) stated that fibronectin promotes endothelial cell activation, survival, migration, and elongation. Fibronectin interacts with integrins via the RGD (Arg-Gly-Asp) motif to form fibrils, and the complex then binds to focal adhesion kinase (FAK) or actin to carry out various cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke has been reported to increase the oxidative stress leading to the dysregulation of reactive oxygen species production as the marker of oxidative stress. 18 Due to the imbalance in the generation and scavenging of ROS, the ROS accumulates leading to tissue damage. 19 Quinine has been reported to be involved in the electron transport chain and decreasing its activity.…”
Section: Discussionmentioning
confidence: 99%